Studi Literatur Review: Penerapan Sentra Persiapan sebagai Upaya Meningkatkan Minat Literasi Baca Tulis pada Anak Usia Dini: Literature Review Study: The Implementation of Preparation Centers as an Effort to Increase Early Literacy Interest in Reading and Writing for Young Children - Ani Naskiki Mulya Dewi; Yuli Kurniawati Sugiyo Pranoto (Universitas Ngudi Waluyo, 2024)
This research is related to efforts to increase the interest in early literacy among preschool children. The aim of the research is to analyze the application of the Sentra Persiapan method as an effort to increase the interest in reading and writing among preschool children. The research uses a literature review approach with the aid of the PICO framework, followed by the use of a prism diagram to obtain a clear and open picture through the process of identifying the composition of the research protocol. The identification includes inclusion and exclusion criteria, resulting in the acquisition of ten articles that have been analyzed for their suitability. The research findings show that the learning method that increases the interest in reading and writing among preschool children. This method creates a captivating and interactive learning environment, uses appropriate teaching materials, and involves active and playful approaches. Collaboration between teachers and parents enhances positive synergy. Various activities help to increase the interest of the children. The strategy for introducing letters and numbers uses media such as songs and random cards to help children understand the basics of reading and writing. ABSTRAK Penelitian ini berkaitan dengan upaya peningkatan minat literasi baca tulis anak usia dini. Tujuan penelitian yaitu menganalisis penerapan sentra persiapan sebagai upaya untuk meningkatkan minat baca tulis pada anak usia dini. Penelitian menggunakan pendekatan literature review dengan bantuan framework PICO, kemudian tahap selanjutnya peneliti menggunakan diagram prisma untuk mendapatkan gambaran yang jelas dan terbuka melalui proses identifikasi penyusunan protokol penelitian. Identifikasi tersebut meliputi kriteria inklusi dan eksklusi dengan memperoleh hasil sepuluh artikel yang telah dianalisis kelayakannya. Hasil penelitian menunjukkan bahwa metode pembelajaran yang meningkatkan minat membaca dan menulis pada anak usia dini. Metode ini menciptakan lingkungan pembelajaran yang menarik dan interaktif, menggunakan bahan ajar yang tepat, dan melibatkan pendekatan bermain dan aktif. Kolaborasi antara guru dan orang tua meningkatkan sinergi positif. Kegiatan yang bervariasi membantu meningkatkan minat anak. Strategi pengenalan huruf dan angka menggunakan media lagu dan kartu acak membantu anak memahami dasar-dasar membaca dan menulis.